2016
DOI: 10.1016/j.molcel.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase Co-Ordinates Carbohydrate Metabolism and Cell Cycle in S. cerevisiae

Abstract: Summary Cyclin Dependent Kinases (CDKs) control cell division in eukaryotes by phosphorylating proteins involved in division. But successful proliferation requires co-ordination between division, and cellular growth in mass. Previous proteomic studies suggested that metabolic proteins, as well as cell division proteins, could potentially be substrates of cyclin dependent kinases. Here we focus on two metabolic enzymes of the yeast S. cerevisiae, neutral trehalase (Nth1) and glycogen phosphorylase (Gph1) and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 57 publications
5
90
0
Order By: Relevance
“…2016; Zhao et al. 2016) and in mammalian cells (Lim and Kaldis 2013; Kaplon, van Dam and Peeper 2015). Building a new cell is dependent on a number of metabolic and biosynthetic reactions which impact on cellular growth, e.g.…”
Section: Perspectives: Integrating Binary Logic With Stoichiometry Tomentioning
confidence: 99%
See 1 more Smart Citation
“…2016; Zhao et al. 2016) and in mammalian cells (Lim and Kaldis 2013; Kaplon, van Dam and Peeper 2015). Building a new cell is dependent on a number of metabolic and biosynthetic reactions which impact on cellular growth, e.g.…”
Section: Perspectives: Integrating Binary Logic With Stoichiometry Tomentioning
confidence: 99%
“…2016; Zhao et al. 2016). Since in vitro experiments suggested a Clb2/Cdk1-mediated phosphorylation of the trehalase Nth1, an activatory effect of Clb2 on Nth1 was simulated, as shown in Fig.…”
Section: Perspectives: Integrating Binary Logic With Stoichiometry Tomentioning
confidence: 99%
“…For instance, Zhao, Chen, Carey, and Futcher (2016) and Ewald, Kuehne, Zamboni, and Skotheim (2016) note that the CDC and metabolism have many regulatory genes in common. Additionally, understanding yeast oscillations and regulation of metabolism is important in the efficient management of bioprocesses (Beuse, Kopmann, Diekmann, & Thoma, 1999;Uchiyama, Morimoto, Yokoyama, & Shioya, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed biochemical models of the growth and division processes within a single fission yeast's cell cycle, including checkpoint controls, were considered in Novak, Csikasz-Nagy, Gyorffy, Chen, and Tyson (1998). Recently, Zhao et al (2016) and Ewald et al (2016) observed that the use of internal carbohydrates is regulated by CDK activity. CDKs have long been known to be primary regulatory agents in the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…It is a very intriguing and sound, intuitively plausible hypothesis that provides good insights into the evolution of phosphorylation sites and was approved by many researchers in the following years (Nishino et al, 2013;Fleurie et al, 2014;Rocha et al, 2014;Chang et al, 2016;Seaman et al, 2016;Zhao et al, 2016). However, there are still some issues that need to be clarified further.…”
mentioning
confidence: 99%